The Use of HPV16-E5, EGFR, and pEGFR as Prognostic Biomarkers for Oropharyngeal Cancer Patients - Taberna, Miren; Torres, Montserrat; Alejo, María; Mena, Marisa; Tous, Sara; Marquez, Sandra; Pavón, Miquel A.; León, Xavier; García, Jacinto; Guix, Marta; Hijano, Rafael; Bonfill, Teresa; et al. (Frontiers in Oncology, 2018)
Background: Anti-epithermal-growth-factor-receptor (EGFR) therapies in combination with radiotherapy are being studied on de-escalation clinical trials for HPV-related oropharyngeal cancer (OPC) patients. The HPV16-E5 oncoprotein increases recycling of activated EGFR to the cell surface, enhancing factor signal transduction. Our aim was to evaluate viral HPV16-E5 oncogene expression as well as EGFR and phosphorylated-EGFR (pEGFR), protein levels as biomarkers for clinical outcome in a retrospective cohort of OPC patients. Methods: Formalin-fixed-paraffin-embedded OPC were collected from 1990 to 2013. OPC samples containing HPV-DNA were subject to viral E6*I mRNA detection and p16INK4a immunohistochemistry (IHC). HPV16-positive cases were evaluated for HPV16-E5 (RT-PCR) and EGFR/pEGFR (IHC). A stratified and matched random sample of HPV-negative samples was used as control and evaluated for EGFR/pEGFR. Overall survival (OS) and disease free survival (DFS) estimates were assessed for locally advanced OPC patients (stage III, IVa,b 7th edition). Results: Among 788 OPC patient samples, 53 were double positive for HPV16-DNA/p16INK4a. HPV16-E5 expression was found in 41 of 53 samples (77.4%). EGFR expression was observed in 37.7% vs 70.8% of HPV16-positive vs HPV-negative samples, respectively; (adjusted OR= 0.15 [95%Confidence Interval=0.04-0.56). Expression of pEGFR followed an inverse pattern with 39.6% and 24.9% detection in HPV16-positive and HPV-negative samples; (adjusted OR=1.58 [95%CI=0.48-5.17]). Within HPV16-positive cases, no association between HPV16-E5/EGFR nor pEGFR was observed. With a median follow-up of 39.36 months (min=0.03-max=272.07), the combination of HPV status and EGFR or pEGFR expression were predictors of better OS (p-value<0.001, for both) and DFS (p-value<0.001 for EGFR and p-value=0.003 for pEGFR). Conclusions: HPV16-E5 is highly expressed on HPV16-positive OPCs. Interestingly, HPV16-positive cases expressed significantly more pEGFR while HPV-negative cases expressed more EGFR. The combinations of HPV status and EGFR or pEGFR may be useful biomarkers for evaluating prognosis outcome in OPC patients.